Micromechanical Behavior of TPMS Scaffolds for Bone Tissue Engineering. Issue 12 (12th October 2020) - Castro, André P. G.; Santos, Jorge; Pires, Tiago; Fernandes, Paulo R.
Abstract: The triply periodic minimal surfaces (TPMS) methodology is explored to design porosity and curvature‐controlled tissue engineering (TE) scaffolds. This work combines mechanical testing and finite element (FE) simulation to characterize TPMS scaffolds micromechanical behavior, i.e., to estimate the response at the cell level to the macromechanical properties of different geometries (Schwartz D, Gyroid, and Schwartz P, with 60%, 70%, and 80% porosity, identified from SD60 to SP80) and testing conditions (6%, 8%, and 10% ramp compression, during 10, 20, and 30 s). Mechanical tests with ten 3D printed samples per model obtain Young Modulus levels from 0.048 GPa (SD80) to 0.267 GPa (SD60) and yield stresses from 0.495 MPa (SP80) to 5.226 MPa (SD60), being these associated with trabecular bone. FE simulations identify strain rate as the major influencer for cell response, as the probabilities for bone formation increase from 23.18% (SD) to 29.81% (SP) when increasing the compression period from 10 to 30 s. Additionally, compression beyond 6% causes excessive rates of cell death. SD and SG models have more consistent cell adhesion paths than SP ones, but superior stiffness of SD scaffolds induces higher cell death probabilities. Thus, SG scaffolds would be a better choice for most TE applications. Abstract : The triply periodic minimal surfaces (TPMS) methodology allows for porosity and curvature‐controlled tissue engineering scaffolds. This work uses mechanical testing and finite element simulation to characterize TPMS scaffolds micromechanical behavior, confirming that the combination of compression rates under 6% and interconnected curved internal structures is favorable for cell adhesion and differentiation into bone and cartilage tissues.